Analisis SWOT dan Penyusunan Rencana Aksi Dalam Audit Risiko Strategis Studi Kasus: PT XYZ. - Jufiter, Remond; Rajagukguk, Wilson; Tewu, M.L. Denny (Universitas Muhammadiyah Pontianak, 2026)
Strategic risk auditing is essential for helping organizations anticipate risks that may affect long-term performance. This study aims to analyze strategic risks at PT XYZ using SWOT analysis, risk assessment, and action plan development. A qualitative case study method was applied through interviews, observation, and document review. The results show that PT XYZ faces key risks related to market competition, operational efficiency, and strategic adaptation. The study implies that integrating SWOT-based risk assessment with a structured action plan can support more effective strategic decision-making and risk mitigation.